If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(x + -3) + -1x + -5 = -5(x + 6) + 13 Reorder the terms: -4(-3 + x) + -1x + -5 = -5(x + 6) + 13 (-3 * -4 + x * -4) + -1x + -5 = -5(x + 6) + 13 (12 + -4x) + -1x + -5 = -5(x + 6) + 13 Reorder the terms: 12 + -5 + -4x + -1x = -5(x + 6) + 13 Combine like terms: 12 + -5 = 7 7 + -4x + -1x = -5(x + 6) + 13 Combine like terms: -4x + -1x = -5x 7 + -5x = -5(x + 6) + 13 Reorder the terms: 7 + -5x = -5(6 + x) + 13 7 + -5x = (6 * -5 + x * -5) + 13 7 + -5x = (-30 + -5x) + 13 Reorder the terms: 7 + -5x = -30 + 13 + -5x Combine like terms: -30 + 13 = -17 7 + -5x = -17 + -5x Add '5x' to each side of the equation. 7 + -5x + 5x = -17 + -5x + 5x Combine like terms: -5x + 5x = 0 7 + 0 = -17 + -5x + 5x 7 = -17 + -5x + 5x Combine like terms: -5x + 5x = 0 7 = -17 + 0 7 = -17 Solving 7 = -17 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 9+-3x=8x+-3x | | 18x-12=8x+16 | | 2760.25/x=2.41 | | 2(2n+1)=3n+8 | | -x-3+4+2x-5=0 | | (6x^4/y)^2 | | 5-2x-3x-7=0 | | 1+-5x=5+8x | | 15(v+4)-3v=4(3v+3)-17 | | g(x)=1/3f(x-4) | | LN=3x+25 | | -0.10(126)+0.90x=0.05(x-14) | | 3x^2=-10x-6 | | 57-3n=21 | | 7[z-(5z+18)+2]=3(z+4) | | -2p-4(3-2p)=2(p-3)-14 | | 2(v+3)=9+v | | n^2+8n-73=-9 | | 9x+9v+8z-6y=xvzy | | 56/16 | | 56*1/16 | | http://media.apexlearning.com/Images/201305/30/9732b49e-38a0-4a46-8791-c144f128dfa4.gif | | c=20*5+100 | | c=30*5+50 | | 1.75m=4 | | X^2/11 | | x^2-2y-24=0 | | x+(x*.01)=1031 | | 2x-2+3= | | 7(8c-1)-16=54c+7 | | 100+2400=c | | 7(x-8)=-7(x-8) |